PENERAPAN PENDEKATAN SCIENTIFIC TERHADAP AKTIVITAS BELAJAR FISIKA SISWAKELAS X SMA NEGERI 3 LUBUKLINGGAU TAHUN PELAJARAN 2018/2019 - Ice Agustin; Ahmad Amin; Wahyu Arini (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
This research is titled "The Application of the Scientific Approach to Physics Learning Activities of Class X Lubuklinggau 3 Senior High School Students in 2018/2019 Academic Year". This study aims to determine the completeness of the physics learning outcomes of class X students of Lubuklinggau 3 Public High School after participating in learning with the Scientific Approach. The research method used is a quasi-experimental method (quasi experiment). The population in this study were all class X of SMA 3 Lubuklinggau SMA 2018/2019 and the sample was class X IPA 4, amounting to 36 students and taken randomly. Data collection is done by techniques observation. Based on the results of the observation analysis at the third meeting with a percentage value of 61,03% with the active category and the fourth meeting with percentage value of 76,06% with a very active category. It can be concluded that the activity of students after applyingthe scientific approach to physics in claas X of SMA Negeri 3 Lubuklinggau academic year 2018/2019 increased.